How to start an antimicrobial stewardship programme in a hospital. (April 2020) - Mendelson, M.; Morris, A.M.; Thursky, K.; Pulcini, C.
Abstract: Background: Antimicrobial stewardship (AMS) describes a coherent set of actions that ensure optimal use of antimicrobials to improve patient outcomes, while limiting the risk of adverse events (including antimicrobial resistance (AMR)). Introduction of AMS programmes in hospitals is part of most national action plans to mitigate AMR, yet the optimal components and actions of such a programme remain undetermined. Objectives: To describe how health-care professionals can start an AMS programme in their hospital, the components of such a programme and the evidence base for its implementation. Sources: National and society-led guidelines on AMS, peer-reviewed publications and experience of AMS experts conducting AMS programmes. Content: We provide a step-by-step pragmatic guide to setting up and implementing a hospital AMS programme in high-income or low-and-middle-income countries. Implications: Antimicrobial stewardship programmes in hospitals are a vital component of national action plans for AMR, and have been shown to significantly reduce AMR, particularly when coupled with infection prevention and control interventions. This step-by-step guide of 'how to' set up an AMS programme will help health-care professionals involved in AMS to optimally design and implement their actions.